MAT264 – Non-parametric Statistics February 2021 - PPSM, Pusat Pengajian Sains Matematik (Universiti Sains Malaysia, 2021)
Please check that this examination paper consists of EIGHTEEN (18) pages of printed material before you begin the examination. Instructions : Answer FOUR (4) questions.